A quantitative survey of water management issues in rural Sindh - Javed, Sheikh Muhammad; Abu Samah, Asnarulkhadi; Redzuan, Marof; Mangrio, Munir Ahmed; Baloch, Lutfullah (University of Sindh Jamshoro, 2015)
Agriculture and water management are of the important tools to poverty reduction among farming communities that helps to provide individual and collective benefits, and enhance quality of life. But in real, the farmers of Sindh province are largely dissatisfied with what they have, indicated by the current situation. Therefore, the researcher focused on the background of farming communities to reveal the facts and figures of rural people connected with water management. In this regard, the crosssectional data were collected on a structured scale through personal interview method, using multi-stage cluster sampling from 457 farmers in Sindh province of Pakistan, and analysis was performed by means of SPSS-20. The results regarding the background of the farmers illustrate that the majority of the farmers aged 36 to 56 were involved in water management activities. In connection with the marital status, an overwhelming majority (98%) of the respondents were married, showing the picture of common rural values, about three fourth (75%) of the respondents are habituated in an extended/joint family system, and a little less than half (47%) of the respondents were illiterate or do not have any formal education. A simple majority (50.5%) of the respondents were landlord-cum-farmers (owner-cultivator), however, an unfair distribution of agricultural land is frequently observed among the farmers in Sindh province of Pakistan. Water logging and salinity was found to be a major issue in the study area as reported by the respondents. Simultaneously, an overwhelming majority of the farmers in Sindh province of Pakistan showed their concern over existing irrigation and drainage system and of the opinion that the institutional corruption and bad governance are hurdled behind the issue.